Visitor motivation in leisure: a study of Saga Hill and Serendah waterfalls, Selangor. / Jane Abi … [et al.] - Abi, Jane; Albattat, Ahmad; Ibrahim, Razali; Mansor, Muhammad Hairol Hakimy; Rosli, Ahmad Faiz (Universiti Teknologi MARA, 2020)
Saga Hill and Serendah Waterfalls have been the popular destination for short leisure gateway for nature enthusiasts in Selangor particularly. Located at Ampang / Cheras District, Saga Hill was a very easy climb features and well maintain trail, a reachable summit of 430 meters and also a waterfall. While Serendah waterfall located at Serendah, attract visitors with a vertical drop of estimated 8 meters waterfall. Serendah waterfall was an ideal site for picnic and hiking activities. Both sites have the attractive nature features and sufficient basic facilities for the convenience of visitors to enhance their experience in outdoor recreational activities participation. The main objective of this study was to identify the visitor’s motivation to visit Saga Hill and Serendah waterfalls. Physical, psychological, sociological and environmental awareness attributes were examined to determine the motivation of visitation to Saga Hills and Serendah waterfalls. The study questionnaire was divided into three section; section A- focuses on the demographic characteristic of the respondents, section B- focuses on the motivational and behavioral aspects of the visitors which consisted physical, psychological, sociological, and environmental variables. The sample of 200 visitors involved in this study based on Simple Random Sampling method to collect data. The primary data were analyzed in a descriptive manner using SPSS 20.0 software. The study suggested both study sites have the same highest mean score for physical, psychological, social and environmental attributes contributing for their leisure participation. Visitors motivated to visit both sites to be healthy, and to increase their fitness. As for the psychological attributes, the visitors agreed that the natural environment and special features of both sites have added value and potentials that increased local tourism industry. The sociological attribute suggested that the visitor’s motivation to visit both sites to enjoy the waterfall with their family and friends. Lastly, environmental attributes also influent the motivation for visitors to Saga Hill and Serendah waterfalls. The development surround both study sites increased their awareness of the importance of maintaining and preserving the natural leisure attractions located within the developed Selangor city. Overall, the result of the study revealed that the main visitor’s motivation to visit Saga Hill and Serendah waterfalls were physical and sociological attributes.